Laser composite additive manufacturing method and application of light heat-resistant high-strength aluminum-based composite material

Through the impact of the impact of dual -laser coupling scanning technology and peak strength pulse laser, the nano -size TIB2, MOSI2, and HFO2 particles are prepared to solve the problem of improving the intensity and thermal resistance of aluminum -based composite materials in existing technologies, and realize light quality , Preparation of high -strength, heat -resistant aluminum -based composite materials.

CN119368759AActive Publication Date: 2025-01-28GUANGDONG POLYTECHNIC NORMAL UNIV +1
View PDF 6 Cites 0 Cited by

Patent Information

Application Number
CN202411390126.4
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-08
Publication Date
2025-01-28
Estimated Expiration
2044-10-08

AI Technical Summary

Technical Problem

The prior art is difficult to prepare nano-sized TiB2, MoSi2, and HfO2 particles, resulting in poor diffusion and strengthening effect of aluminum-based composite materials and unable to effectively improve their strength and heat resistance.

Method used

Adopt continuous and peak strength pulse dual -laser coupling scanning technology to prepare TIB2, TIB, MOSI2, and HFO2 particles with nano -size. And metallurgical defects.

Benefits of technology

Successfully prepared a light -quality high -strength heat -resistant aluminum base composite material with fine crystal tissue, which significantly improved its tensile strength and ductility, and has good high temperature resistance.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119368759A_ABST
    Figure CN119368759A_ABST
Patent Text Reader

Abstract

The invention discloses a laser composite additive manufacturing method and application of a light heat-resistant high-strength aluminum-based composite material. The method comprises the steps that oxygen in a printing sealed cabin is pumped out, and then argon is introduced to balance the air pressure difference between the interior and the exterior of the printing cabin; coupling laser beams output by the pulse fiber laser and the continuous fiber laser, and adjusting the coupled laser beams; selectively melting the aluminum-based composite powder on the substrate by using the adjusted and focused coupling laser beam; after the single layer of the to-be-printed aluminum-based composite material is cooled and solidified, TiB2 powder is laid on the surface of the single layer of the to-be-printed aluminum-based composite material, light-transmitting quartz glass is pressed on the TiB2 powder in a covering mode, and then pulse laser penetrates through the quartz glass to irradiate the TiB2 powder in an out-of-focus mode so as to generate high-explosion plasma; the heat-force coupling effect of selective melting of coupled laser beams and shock strengthening of defocused pulse laser are interacted layer by layer and are repeated in sequence. Coupled laser and single pulse laser are combined for use, and the light heat-resistant high-strength aluminum-based composite material is prepared.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to the technical field of laser additive manufacturing and the technical field of metal composite material preparation, and in particular relates to a laser composite additive manufacturing method and application of a lightweight, heat-resistant and high-strength aluminum-based composite material. Background Art

[0002] With the continuous development of cutting-edge industries such as aerospace, the demand for improving the high-temperature strength and heat resistance of metal structural parts has become more urgent. In this context, ceramic particle reinforced aluminum matrix composites (AMCs) have become the focus, with excellent properties such as light weight, high specific strength and specific stiffness, good thermal stability, good wear resistance and corrosion resistance. Among them, titanium diboride (TiB2) particles, as an ideal high thermal stability dispersion strengthening phase material, have high melting point, high strength, good chemical stability and good compatibility with aluminum matrix. Under high temperature conditions, MoSi2 can react with aluminum alloy to form a high-temperature oxidation protection film, and HfO2 can purify the grain boundaries of the aluminum alloy matrix and improve its high-temperature cracking resistance, making TiB2, MoSi2, and HfO2 particles important research objects.

[0003] However, there are a series of challenges in improving the strength and heat resistance of the above-mentioned particle-reinforced aluminum-based composites, mainly due to the fact that nano-sized particles have the best dispersion strengthening effect on aluminum-based composites, but are difficult to prepare. Existing research has mainly focused on improving the preparation process, including stirring and melting, powder metallurgy, and additive manufacturing technology. These methods have certain limitations in the dispersion, morphology, and size of the reinforcing particles, which affects the performance of the composites. In the stirring and melting method, the agglomeration of nanoparticles, the stress concentration caused by the irregular shape of the particles, and the introduction of gas and impurities have become restrictive factors. Although the powder metallurgy method can achieve uniform dispersion of nanoparticles, it is costly and difficult to carry out industrial production. In the single continuous laser selective melting forming process, since the melting point of TiB2, MoSi2, and HfO2 particles is much higher than that of the aluminum matrix material, increasing the energy density of the high-energy beam continuous laser will only increase the melting of the aluminum matrix and expand the molten pool area, but cannot change the morphology of the TiB2, MoSi2, and HfO2 reinforced particles. Most of the reinforced particles always exist in the molten pool in the original solid non-nanoscale powder particle form, and nano-sized particles cannot be obtained, and the dispersion strengthening effect is poor. Summary of the invention

[0004] In order to address the deficiencies of the above-mentioned prior art, the present invention provides a laser composite additive manufacturing method and application of a lightweight, heat-resistant, high-strength aluminum-based composite material, which utilizes continuous and high-peak intensity pulse dual laser coupling scanning to prepare an aluminum alloy block layer with nano-sized TiB2, TiB, MoSi2 and HfO2 particle dispersion strengthening, and then utilizes the impact strengthening and large plastic deformation effect of high-peak intensity pulsed laser to eliminate the internal stress and metallurgical defects of the block layer layer by layer, thereby preparing a lightweight, high-strength, heat-resistant, high-performance aluminum-based composite material with a fine-grained structure.

[0005] The first object of the present invention is to provide a laser composite additive manufacturing method for a lightweight, heat-resistant, high-strength aluminum-based composite material.

[0006] The second object of the present invention is to provide a lightweight, heat-resistant and high-strength aluminum-based composite material.

[0007] The third object of the present invention is to provide an application of a lightweight, heat-resistant, high-strength aluminum-based composite material.

[0008] The first object of the present invention can be achieved by adopting the following technical solutions: A laser composite additive manufacturing method for a lightweight, heat-resistant, high-strength aluminum-based composite material, the method comprising: Extract the oxygen in the printing chamber and introduce argon to balance the pressure difference inside and outside the chamber. The laser beams output by the pulse fiber laser and the continuous fiber laser are coupled, and the coupled laser beams are adjusted to ensure the consistency of the laser beam focus spot size and energy density on the substrate; according to the generated two-dimensional scanning trajectory, the adjusted focused coupled laser beam is used to selectively melt the aluminum-based composite powder and print it in lanes and layers on the preheated substrate; wherein the aluminum-based composite powder is micron TiB2, MoSi2, HfO2 particles dispersed in AlSi10Mg powder, and the mass ratios thereof are 5~8wt.%, respectively. 3~5wt.%, 1~2wt.% and 85~91wt.%; the process parameters of the adjusted focused coupled laser beam selective melting are: scanning speed of 1000~2000mm / s, overlap rate of 20~50%, layer thickness of 20~30μm, and the coupling laser rotation angle of 67° or 90° during interlayer scanning. The pulsed laser induces the precipitation of high melting point TiB2, MoSi2, HfO2 micron particles in various ways to form nano-sized TiB2, TiB, MoSi2 and HfO2 reinforcement particles; After the single layer of aluminum-based composite material to be printed is cooled and solidified, a layer of TiB2 powder is laid on the surface thereof, and a transparent quartz glass is pressed on the TiB2 powder, and then a single high-peak intensity pulse laser is used to defocus and irradiate the TiB2 powder through the quartz glass to generate high-explosive plasma, so that the printed single-layer composite material is subjected to the shock strengthening large plastic deformation effect generated by the defocused single pulse laser to eliminate internal stress and metallurgical defects; the process parameters of the defocused single pulse laser shock strengthening are: pulse repetition frequency of 1Hz to 10kHz, scanning speed of 1 to 100mm / s, overlap rate of 20 to 50%, and layer thickness of 15 to 20μm; The thermal-mechanical coupling effect of the adjusted focused coupled laser beam selective melting and the defocused single high peak intensity pulse laser shock strengthening is used to interact layer by layer and repeat in sequence until the size of the prepared lightweight, heat-resistant and high-strength aluminum-based composite material meets the requirements.

[0009] Furthermore, when the adjusted focused coupled laser beam is used for selective melting, the laser beams output by the pulse fiber laser and the continuous fiber laser are coupled through the optical fiber, and the setting parameters of the pulse fiber laser are: the central wavelength is 1064nm, the laser power is 10-100W, the peak pulse width is 1-100ns, the pulse repetition frequency is 1kHz, and the focused spot diameter is 25μm; the setting parameters of the continuous fiber laser are: the central wavelength is 1064nm, the laser power is 100-500W, the maximum modulation frequency is 100kHz, and the focused spot diameter is 50μm.

[0010] Furthermore, when a defocused single pulse laser is used for shock strengthening, the setting parameters of the pulse fiber laser are: a central wavelength of 1064 nm, a laser power of 10 to 100 W, a pulse repetition frequency of 1 Hz to 10 kHz, and a defocused laser spot diameter of 800 to 1200 μm.

[0011] Furthermore, the aluminum-based composite powder is obtained by the following method: TiB2, MoSi2, HfO2 micron particles and titanium alloy powder in a set proportion are mixed, and then the mixed powder is mechanically ball-milled at room temperature under an argon protective atmosphere to disperse the TiB2, MoSi2, HfO2 micron particles in the titanium alloy powder; the mixed powder after room temperature mechanical ball milling is low-temperature mechanical ball-milled in liquid nitrogen to obtain an ultrafine near-spherical aluminum-based composite powder that meets the requirements of laser selective melting forming, and finally vacuum dried.

[0012] Furthermore, the average particle size of micron TiB2, MoSi2, and HfO2 is 1~3μm, and the average particle size of aluminum-based alloy powder is 15~53μm.

[0013] Furthermore, the chemical composition of the micron TiB2 particle powder is (wt.%): B ≥30.0%, O ≤1.0%, C ≤0.1%, and the balance is Ti; the chemical composition of the micron MoSi2 particle powder is (wt.%): Si ≥36.0%, O ≤0.15%, C ≤0.03%, and the balance is Mo; the chemical composition of the micron HfO2 particle powder is (wt.%): O ≥15.0%, S ≤1.0%, and the balance is Hf; the chemical composition of the AlSi10Mg powder is (wt.%): Si 9.0~11.0%, Mg 0.2~0.45%, Fe ≤0.55%, Mn ≤0.45%, Zn ≤0.1%, and the balance is Al.

[0014] Furthermore, in lightweight, heat-resistant, high-strength aluminum-based composite materials, TiB2 and TiB are uniformly dispersed in the refined aluminum matrix in the form of nano-sized spherical particles, which refines the aluminum matrix grains to form a fine-grain strengthening effect, which is beneficial to the dispersion strengthening effect of TiB2 and TiB; nano-sized MoSi2 and HfO2 are both dispersed at the grain boundaries of α-Al, and nano-MoSi2 will react with Al under high temperature conditions to form an excellent high-temperature resistant protective film, and nano-HfO2 can significantly purify the grain boundaries to improve its crack resistance.

[0015] Furthermore, the average particle size of the nano-sized TiB2, TiB, MoSi2 and HfO2 reinforcement particles is 300-800 nm.

[0016] The second object of the present invention can be achieved by adopting the following technical solutions: A lightweight, heat-resistant, high-strength aluminum-based composite material is prepared based on the above-mentioned laser composite additive manufacturing method.

[0017] The third object of the present invention can be achieved by adopting the following technical solutions: An application of a lightweight, heat-resistant, high-strength aluminum-based composite material, and an application of the lightweight, heat-resistant, high-strength aluminum-based composite material prepared by the above-mentioned laser composite additive manufacturing method in the fields of aerospace, rail transportation, and electronic industry technology.

[0018] The present invention has the following beneficial effects compared with the prior art: 1. Compared with the single laser technology that only relies on heat input characteristics for selective melting using continuous laser, when the high melting point TiB2, MoSi2, HfO2 reinforcement phase and aluminum matrix composite powder with very different thermal properties are selectively melted, the above reinforcement phase always exists in the aluminum liquid matrix in a solid form and does not undergo physical state transformation, and the aluminum-based material has a high reflectivity, so nano-sized particles cannot be obtained; the present invention first uses continuous / pulse dual laser coupling to print aluminum-based material composite powder with dispersed distribution of ultrafine TiB2, MoSi2, HfO2 particles, and uses continuous / pulse composite laser to induce extraordinary composite effects such as material thermal deposition, plasma excitation activation and compressive stress shock wave to cause TiB2, MoSi2, HfO2 to undergo physical state transformation , the solid state of micron-sized particles is transformed into plasma and liquid phase, and multiple physical components coexist in the aluminum liquid matrix. During the rapid solidification process, a large number of nano-sized TiB2, TiB, MoSi2 and HfO2 strengthening phase particles will be precipitated in various ways such as electrolysis, solid solution precipitation, and secondary precipitation. The interface bonding strength between the strengthening phase and the aluminum matrix is ​​high; after the dual laser scanning forming layer is cooled and solidified, a layer of TiB2 powder is laid on its surface and covered with transparent quartz glass, and a single high peak intensity pulse laser is continued to be used to irradiate the newly laid TiB2 powder through the quartz glass to form a high explosive plasma, so that the dual laser coupling scanning forming layer is subjected to the impact strengthening large plastic deformation effect generated by a single pulse laser to eliminate the internal stress and metallurgical defects of the block layer; 2. In the aluminum-based composite material prepared by the present invention, TiB2 and TiB are uniformly dispersed in the refined aluminum matrix in the form of nano-sized spherical particles, so as to refine the aluminum matrix grains and form a fine-grain strengthening effect, which is beneficial for TiB2 and TiB to better play the role of dispersion strengthening and improve the mechanical properties of the material; and nano-TiB2 and TiB are firmly combined with the aluminum matrix, and there is no adverse reaction at the interface; nano-sized MoSi2 and HfO2 are both dispersed at the grain boundaries of α-Al, and nano-MoSi2 will react with Al under high temperature conditions to form an excellent high-temperature resistant protective film, and nano-HfO2 can significantly purify the grain boundaries to improve its crack resistance. BRIEF DESCRIPTION OF THE DRAWINGS

[0019] In order to more clearly illustrate the embodiments of the present invention or the technical solutions in the prior art, the drawings required for use in the embodiments or the description of the prior art will be briefly introduced below. Obviously, the drawings described below are only some embodiments of the present invention. For ordinary technicians in this field, other drawings can be obtained based on the structures shown in these drawings without paying creative work.

[0020] Figure 1 A schematic diagram of a dual laser coupled selective melting process for forming nanoparticle (TiB2 as an example) dispersion-strengthened aluminum-based composite material according to an embodiment of the present invention; Figure 2 This is a scanning electron microscope image of an aluminum-based material composite powder with dispersed ultrafine particles (taking TiB2 as an example) according to an embodiment of the present invention. DETAILED DESCRIPTION

[0021] In order to make the purpose, technical solution and advantages of the embodiments of the present invention clearer, the technical solution in the embodiments of the present invention will be described clearly and completely below. Obviously, the described embodiments are part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments in the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention. It should be understood that the specific embodiments described are only used to explain the present application and are not used to limit the scope of the present application.

[0022] Example: The laser composite additive manufacturing method for the lightweight, heat-resistant, high-strength aluminum-based composite material provided in this embodiment can be referred to Figure 1 , specifically including the following steps: (1) Preparation of aluminum-based composite powder.

[0023] The original purity of TiB2 powder, MoSi2 powder and HfO2 powder is above 99.5%, and the average particle size is 1μm~3μm; the purity of aluminum-based powder is above 99.5%, and the average particle size is 15μm~53μm. Among them, the chemical composition of TiB2 particle powder is (wt.%): B ≥ 30.0%, O ≤ 1.0%, C ≤ 0.1%, and the balance is Ti; the chemical composition of MoSi2 particle powder is (wt.%): Si ≥ 36.0%, O ≤ 0.15%, C ≤ 0.03%, and the balance is Mo; the chemical composition of HfO2 particle powder is (wt.%): O ≥ 15.0%, S ≤ 1.0%, and the balance is Hf; the aluminum-based powder is AlSi10Mg powder, and its chemical composition is (wt.%): Si 9.0~11.0%, Mg 0.2~0.45%, Fe ≤ 0.55%, Mn ≤ 0.45%, Zn ≤ 0.1%, and the balance is Al.

[0024] In this embodiment, the original purity of TiB2 powder, MoSi2 powder and HfO2 powder selected are all above 99.5%, and the average particle size is 3μm; the purity of aluminum-based powder is above 99.5%, and the average particle size is 15μm. The chemical composition of TiB2 particle powder is (wt.%): B is 30.0%, O is 1.0%, C is 0.1%, and the balance is Ti; the chemical composition of MoSi2 particle powder is (wt.%): Si is 36.0%, O is 0.15%, C is 0.03%, and the balance is Mo; the chemical composition of HfO2 particle powder is (wt.%): O is 15.0%, S is 1.0%, and the balance is Hf; the aluminum-based powder is AlSi10Mg powder, and its chemical composition is (wt.%): Si is 10.0%, Mg is 0.30%, Fe is 0.55%, Mn is 0.45%, Zn is 0.10%, and the balance is Al.

[0025] A mixed powder consisting of 5~8wt.% TiB2 powder, 3~5wt.% MoSi2 powder, 1~2wt.% HfO2 powder and 85~91wt.% AlSi10Mg powder was mixed for 240 minutes using a powder mixer at a mixing speed of 12rpm. After being taken out, it was dried to obtain an aluminum-based composite powder with dispersed ultrafine TiB2, MoSi2 and HfO2 particles.

[0026] The mass ratio of TiB2 powder, MoSi2 powder, HfO2 powder and AlSi10Mg powder selected in this embodiment is 5:3:2:90.

[0027] The scanning electron microscopy of the aluminum-based composite powder (using TiB2 as an example) prepared in this embodiment can be referred to Figure 2 , TiB2 powder and AlSi10Mg powder are mixed evenly without a large amount of agglomeration.

[0028] (2) A three-dimensional model is established based on the lightweight, heat-resistant, and high-strength aluminum-based composite material to be prepared, and layered slicing is performed. A series of two-dimensional scanning trajectories for laser selective melting are generated based on the slice contour information.

[0029] (3) Based on the generated two-dimensional scanning trajectory, dual laser coupled selective melting is used to print the aluminum-based composite powder in lanes and layers on the substrate.

[0030] Specifically, the aluminum-based composite powder is loaded into the loading hopper of the automatic powder feeding machine; the printing sealed cabin is cleaned before the experiment and the substrate plane is adjusted. The printing sealed cabin is evacuated to a vacuum so that the oxygen content is less than 1000ppm; and then argon gas is filled to balance the pressure difference inside and outside the printing cabin. In this embodiment, the residual oxygen content in the printing sealed cabin is 100ppm.

[0031] The process parameters of dual laser coupled selective melting in this embodiment are: the scanning speed of the coupled laser beam is 1500mm / s, the overlap rate is 50%, the layer thickness is 20μm, the coupled laser rotation angle is 90° during interlayer scanning, and the pulsed laser induces the high melting point TiB2, MoSi2, HfO2 micron particles to precipitate in various ways to form nano-sized TiB2, TiB, MoSi2 and HfO2 enhanced particles. Among them, the parameters of the pulse fiber laser are: wavelength of 1064nm, laser power of 50W, pulse width of 10ns, pulse repetition frequency of 1kHz, and focus spot diameter of 25μm; the parameters of the continuous fiber laser are: wavelength of 1064nm, laser power of 300W, focus spot diameter of 50μm, modulation frequency of 100kHz; the composite laser energy density is 78.24J / mm 3 .

[0032] (4) After the coupled laser scanning forming layer is cooled and solidified, a layer of TiB2 powder is laid on its surface and covered with transparent quartz glass. A single high peak intensity pulse laser is used to irradiate the newly laid TiB2 powder through the quartz glass to form a high explosive plasma, which produces a large plastic deformation effect of impact strengthening. The internal stress and metallurgical defects of the block layer are eliminated layer by layer by using the large plastic deformation effect of the impact strengthening of the high peak intensity pulse laser. The thermal-mechanical coupling effect of dual laser coupled selective melting and single pulse laser shock strengthening is alternated layer by layer, and reciprocated in sequence, and finally a lightweight, heat-resistant, high-strength aluminum-based composite material with a fine-grained structure is obtained.

[0033] In this embodiment, the process parameters of high peak intensity pulsed laser shock peening are as follows: the defocused laser spot diameter is 1000 μm, the pulse repetition frequency is 100 Hz, the scanning speed is 10 mm / s, the overlap rate is 25%, and the layer thickness is 20 μm.

[0034] The microstructure characterization and mechanical properties analysis of lightweight, heat-resistant, high-strength aluminum-based composite materials yielded the following conclusions: Scanning electron microscopy (SEM) was used to characterize the microstructure and study the typical microstructure. The SEM images of the cladding layer prepared by TiB2, MoSi2, HfO2 and AlSi10Mg and the original AlSi10Mg alloy were analyzed. The results show that the original AlSi10Mg alloy has a columnar unit cell morphology; while the microstructure of the AlSi10Mg alloy reinforced with TiB2, MoSi2, and HfO2 particles shows that the unit cell is a uniform ultrafine equiaxed crystal with no obvious directionality. At the common vertices of multiple unit cells, some nanoparticles can be seen clustered together. In addition, the grain size and area were determined by electron backscattering device (EBSD). The image after the sample was magnified showed that a large number of nanostructured particles were observed to be in a cubic prism shape with a particle size of less than 500nm; in the AlSi10Mg alloy reinforced with TiB2, MoSi2, and HfO2 particles, about 40% of the grains were less than 1μm, and the average diameter was about 2.1μm.

[0035] In terms of mechanical properties analysis, the dog-bone tensile test specimens were machined according to the ASTM-E8M standard, and the experiments were carried out on the Zwick / RoellZ100 testing machine. The AlSi10Mg alloys reinforced with TiB2, MoSi2, and HfO2 particles and the original AlSi10Mg alloy samples were subjected to tensile tests. Specifically, the room temperature tensile strength of the original AlSi10Mg alloy is about 490MPa, and the elongation is 3.7%; the room temperature tensile strength and elongation of the AlSi10Mg strengthened by TiB2, MoSi2, and HfO2 are significantly enhanced, which are 530MPa and 8%, respectively, and the tensile strength at 420°C is 155MPa. Therefore, the tensile strength and ductility of the AlSi10Mg composite material strengthened by TiB2, MoSi2, and HfO2 are significantly improved at the same time, and it has good high temperature strength resistance. Therefore, through multiple effects such as fine grain strengthening and solid solution strengthening, a lightweight, high-strength, heat-resistant, lightweight, heat-resistant, and high-strength aluminum-based composite material with fine grain structure is finally formed.

[0036] The microstructural characteristics of the lightweight, heat-resistant, high-strength aluminum-based composite material prepared in this embodiment are as follows: the metal matrix is ​​composed of fine equiaxed crystals, about 40% of the grains are less than 1 μm in size, and the average diameter is about 2.1 μm; due to a series of nonlinear effects generated by the composite action of the dual lasers, nanoparticles are precipitated in various ways such as electrochemical precipitation, solid solution precipitation, and secondary precipitation, and nano-sized TiB2, TiB, MoSi2 and HfO2 particles are evenly distributed at the grain boundaries of the metal matrix.

[0037] In summary, the present invention adopts prefabricated aluminum-based composite powder with dispersed ultrafine TiB2, MoSi2, and HfO2 particles, and utilizes the thermal deposition, photo-induced plasma excitation activation, and compressive stress shock wave extraordinary composite effects under the composite action of high peak intensity pulse / continuous dual lasers to rapidly heat the composite powder to a high temperature, so that TiB2, MoSi2, and HfO2 coexist in the aluminum liquid matrix in the form of plasma and liquid phase. Nano-sized TiB2, MoSi2, TiB, and HfO2 particles are precipitated during the rapid solidification process. After the dual laser coupling scanning forming layer is cooled and solidified, the surface is again heated to a high temperature. A layer of TiB2 powder is laid, and then covered with translucent quartz glass. A single high peak intensity pulsed laser is continuously used to irradiate the newly laid TiB2 powder through the quartz glass to form a high explosive plasma, so that the dual laser coupled scanning forming layer is then subjected to the large plastic deformation effect of the impact strengthening produced by the single pulsed laser. The large plastic deformation effect of the impact strengthening of the high peak intensity pulsed laser is used to eliminate the internal stress and metallurgical defects of the block layer layer by layer. The thermal-mechanical coupling effect of the dual laser coupled selective melting and the pulsed single laser shock strengthening is interactive layer by layer, and reciprocates in sequence, and finally a lightweight, high-strength, heat-resistant, high-strength aluminum-based composite material with a fine-grained organizational structure is prepared. The present invention is expected to provide solutions with academic value and practical application prospects for important industrial fields such as aerospace in terms of solving technical problems, optimizing process parameters, and establishing new systems and preparation processes.

[0038] The above is only a preferred embodiment of the present invention, but the protection scope of the present invention is not limited thereto. Any technician familiar with the technical field can make equivalent replacements or changes according to the technical solution and inventive concept of the present invention within the scope disclosed by the present invention, which shall fall within the protection scope of the present invention.

Claims

1. A laser composite additive manufacturing method for a lightweight, heat-resistant, high-strength aluminum-based composite material, characterized in that: The method comprises: Extract the oxygen in the printing chamber and introduce argon to balance the pressure difference inside and outside the chamber. The laser beams output by the pulse fiber laser and the continuous fiber laser are coupled, and the coupled laser beams are adjusted to ensure the consistency of the laser beam focus spot size and energy density on the substrate; according to the generated two-dimensional scanning trajectory, the adjusted focused coupled laser beam is used to selectively melt the aluminum-based composite powder and print it in lanes and layers on the preheated substrate; wherein the aluminum-based composite powder is micron TiB2, MoSi2, HfO2 particles dispersed in AlSi10Mg powder, and the mass ratios thereof are 5~8wt.%, respectively. 3~5wt.%, 1~2wt.% and 85~91wt.%; the process parameters of the adjusted focused coupled laser beam selective melting are: scanning speed of 1000~2000mm / s, overlap rate of 20~50%, layer thickness of 20~30μm, and the coupling laser rotation angle of 67° or 90° during interlayer scanning. The pulsed laser induces the precipitation of high melting point TiB2, MoSi2, HfO2 micron particles in various ways to form nano-sized TiB2, TiB, MoSi2 and HfO2 reinforcement particles; After the single layer of aluminum-based composite material to be printed is cooled and solidified, a layer of TiB2 powder is laid on the surface thereof, and a transparent quartz glass is pressed on the TiB2 powder, and then a single high-peak intensity pulse laser is used to defocus and irradiate the TiB2 powder through the quartz glass to generate high-explosive plasma, so that the printed single-layer composite material is subjected to the shock strengthening large plastic deformation effect generated by the defocused single pulse laser to eliminate internal stress and metallurgical defects; the process parameters of the defocused single pulse laser shock strengthening are: pulse repetition frequency of 1Hz to 10kHz, scanning speed of 1 to 100mm / s, overlap rate of 20 to 50%, and layer thickness of 15 to 20μm; The thermal-mechanical coupling effect of the adjusted focused coupled laser beam selective melting and the defocused single high peak intensity pulse laser shock strengthening is used to interact layer by layer and repeat in sequence until the size of the prepared lightweight, heat-resistant and high-strength aluminum-based composite material meets the requirements.

2. The method according to claim 1, characterized in that When the adjusted focused coupled laser beam is used for selective melting, the laser beams output by the pulse fiber laser and the continuous fiber laser are coupled through the optical fiber. The setting parameters of the pulse fiber laser are: the central wavelength is 1064nm, the laser power is 10-100W, the peak pulse width is 1-100ns, the pulse repetition frequency is 1kHz, and the focus spot diameter is 25μm; the setting parameters of the continuous fiber laser are: the central wavelength is 1064nm, the laser power is 100-500W, the maximum modulation frequency is 100kHz, and the focus spot diameter is 50μm.

3. The method according to any one of claims 1 and 2, characterized in that: When a defocused single pulse laser is used for shock strengthening, the setting parameters of the pulse fiber laser are: a central wavelength of 1064nm, a laser power of 10-100W, a pulse repetition frequency of 1Hz-10kHz, and a defocused laser spot diameter of 800-1200μm.

4. The method according to claim 1, characterized in that: The aluminum-based composite powder is obtained by the following method: TiB2, MoSi2, HfO2 micron particles and titanium alloy powder in a set proportion are mixed, and then the mixed powder is mechanically ball-milled at room temperature under an argon protective atmosphere to disperse the TiB2, MoSi2, HfO2 micron particles in the titanium alloy powder; the mixed powder after room temperature mechanical ball milling is low-temperature mechanical ball-milled in liquid nitrogen to obtain an ultrafine near-spherical aluminum-based composite powder that meets the requirements of laser selective melting forming, and finally vacuum dried.

5. The method according to any one of claims 1 and 4, characterized in that: The average particle size of micron TiB2, MoSi2, and HfO2 is 1~3μm, and the average particle size of aluminum-based alloy powder is 15~53μm.

6. The method according to any one of claims 1 and 4, characterized in that: The chemical composition of micron TiB2 particle powder is (wt.%): B ≥30.0%, O ≤1.0%, C ≤0.1%, and the balance is Ti; the chemical composition of micron MoSi2 particle powder is (wt.%): Si ≥36.0%, O ≤0.15%, C ≤0.03%, and the balance is Mo; the chemical composition of micron HfO2 particle powder is (wt.%): O ≥15.0%, S ≤1.0%, and the balance is Hf; the chemical composition of AlSi10Mg powder is (wt.%): Si 9.0~11.0%, Mg 0.2~0.45%, Fe ≤0.55%, Mn ≤0.45%, Zn ≤0.1%, and the balance is Al.

7. The method according to claim 1, characterized in that In lightweight, heat-resistant, high-strength aluminum-based composite materials, TiB2 and TiB are uniformly dispersed in the refined aluminum matrix in the form of nano-sized spherical particles, which refines the aluminum matrix grains to form a fine-grain strengthening effect, which is beneficial to the dispersion strengthening effect of TiB2 and TiB; nano-sized MoSi2 and HfO2 are both dispersed at the grain boundaries of α-Al, and nano-MoSi2 will react with Al under high temperature conditions to form an excellent high-temperature resistant protective film, and nano-HfO2 can significantly purify the grain boundaries to improve its crack resistance.

8. The method according to any one of claims 1 and 7, characterized in that: The average particle size of the nano-sized TiB2, TiB, MoSi2 and HfO2 reinforcing particles is 300-800 nm.

9. A lightweight, heat-resistant, high-strength aluminum-based composite material, characterized in that: It is prepared based on the laser composite additive manufacturing method described in any one of claims 1 to 8.

10. An application of a lightweight, heat-resistant, high-strength aluminum-based composite material, characterized in that: Application of the lightweight, heat-resistant, high-strength aluminum-based composite material prepared by the laser composite additive manufacturing method according to any one of claims 1 to 8 or the lightweight, heat-resistant, high-strength aluminum-based composite material according to claim 9 in the fields of aerospace, rail transportation, and electronic industry technology.

Citation Information

Patent Citations

  • Multifunctional laser selective melting forming device

    CN110315078A

  • Online heat treatment process for metal additive manufacturing

    CN110434332A

  • Selective laser melting and laser shock strengthening composite additive manufacturing equipment and method

    CN113976925A

  • Method and device for pulse-continuous laser composite additive manufacturing of high-performance titanium-based alloy

    CN118060557A

  • Double-laser melting and forging additive remanufacturing method for roller gradient wear-resistant strengthened layer

    CN118513566A